PERBUATAN TERCELA SEBAGAI ALASAN PEMAKZULAN PRESIDEN DAN/ATAU WAKIL PRESIDEN - Hufron (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
Six reasons of impeachment of the President and /or Vice President in Article 7 UUD 1945, namely (1) treason against the state, (2) corruption, (3) bribery, (4) other felonies; (5) misdemeanor; and (6) no longer qualify as the President and / or Vice President, there is one reason that the formulation of norms are abstract and vague, can result in a variety (multiple interpretations), that is to